Fatmawati Sukarno : the first lady - Nugroho, Arifin Suryo, 1985- (Yogyakarta : Ombak, 2010)
Biography of Fatmawati Sukarno, one of Soekarno's wives, the first president of Indonesia.
Includes bibliographical references (p. 263-267) and index.
Includes bibliographical references (p. 263-267) and index.
Keywords: Sukarno, Fatmawati, -- 1923-1980 -- Biography; Soekarno, -- 1901-1970.; Presidents' spouses -- Indonesia -- Biography; Women -- Indonesia -- Biography